Sistem Informasi Manajemen dalam Mendukung Layanan Administrasi di Sekolah - Malik, Wildan Maulana; Chotimah, Chusnul; Junaris, Imam (AKSI: Jurnal Manajemen Pendidikan Islam, 2024)
Era now this, improvement institution education need exists technology that works for support school so own power competitive. Head school need use system information management because often faced on situation increasing education​ complicated. System the very required in education for manage service school like administration related to student, teacher and data means and infrastructure. Writing Writing article this aim for discuss in a way complete about how system information management can support service administration at school. Method in article this use studies references with method gather information from various relevant sources​ in accordance topic study. Method analysis fill used on stage data processing with method analyze meaning and content from a number of type library obtained.​ Results study already show that head school need apply system information management to make it easier in give enhancement activity in a way effective with do various function management. Field administration must prepare three officer in apply system the for service administration that is part collection, processing and data storage. Factors that become supporter in application matter the is Source Power Man management, facilities school and school programs. Whereas factors that become the barrier is Source Power Man users, servers and data synchronization.